Educational Games for Learning Mathematics Medium at Elementary School Level - Ardyani, Benedikta Avien; Pamudji, Andre Kurniawan; Prasetya, FX. Hendra (Soegijapranata Catholic University, 2024)
Observation data shows various problems experienced by elementary school students when learning about Greatest Common Factor (GCF) and Least Common Multiple (LCM). This research aims to: (1) understand the effectiveness of learning math through education game, (2) introduce technology to students without interrupting their regular study time, and (3) increase students’ interest in learning math through education game. Sample used were 62 students in grade 5 and 6. The method of this research uses 4 variables, i.e. Performance Expectancy (PE), Effort Expectancy (EE), Hedonic Motivation (HM), and Behavioral Intention (BI). After the respondents have tried playing the game, they fill out Google form and the result obtained with 51 respondents.